Baicalein combined with azoles against fungi in vitro - Liang, Mengmin; Hu, Qingwen; Yu, Junhao; Zhang, Heng; Liu, Sijie; Huang, Jiangrong; Sun, Yi (Frontiers in Microbiology, 2025)
BackgroundInvasive fungal infections (IFIs) constitute a significant health challenge, particularly among immunocompromised individuals, characterized by a high prevalence and associated mortality rates. The synergistic administration of Baicalein (BE) with azole antifungal agents could potentially herald a novel therapeutic paradigm.Materials and methods54 Aspergillus strains and 23 strains of dematiaceous fungi were selected. The standard M38-A2 microbroth dilution method was used to test the minimum inhibitory concentration (MIC) and the fractional inhibitory concentration index (FICI) of fungi when BE combined with itraconazole (ITC), voriconazole (VRC), posaconazole (POS) and Isavuconazole (ISV).ResultsBE shows synergistic effects with POS and ITC, with 89.61% and 25.97% of fungal strains. The BE/POS regimen exerted synergistic effects in 87.04% of Aspergillus and an impressive 95.65% of dematiaceous fungi. In comparison, the BE/ITC combination showed significantly lower synergy, affecting 33.33% of Aspergillus and a mere 8.70% of dematiaceous strains. Antagonistic interactions were sporadically observed with BE in combination with ITC, VRC, POS and ISV. Within the azole class, the BE/POS pairing stood out for its frequent synergistic activity, in contrast to the absence of such effects when BE was paired with VRC or ISV. Highlighting the potential of BE/POS as a notably effective antifungal strategy.ConclusionIn vitro, BE/POS combination emerged as the most effective antifungal strategy, exhibiting synergistic effects in the majority of Aspergillus and dematiaceous fungi strains, whereas BE/ITC showed significantly less synergy, and BE with VRC or ISV displayed no synergistic activity.